Fluid and metal sources of the Changfagou porphyry copper deposit, southern Jilin Province, NE China: Constraints from fluid inclusions and H‐O‐S‐Pb isotope systematics - Zhang, Yong; Xing, Shuwen; Song, Quanheng; Yu, Zhengtao; Liang, Shifu; Liu, Y. (Geological journal (Chichester, England), 2018)
The Changfagou copper deposit, a newly discovered porphyry deposit in the southern Jilin Province, NE China, is tectonically located on the northeastern margin of the North China Block. We recognized four types of sulfide‐quartz veins at Changfagou, including quartz–K‐feldspar–magnetite veins (Stage I), quartz–molybdenite–pyrite–chalcopyrite veins (Stage II), quartz–chalcopyrite–pyrite–galena–sphalerite veins (Stage III), and quartz–carbonate veins (Stage IV). Three types of fluid inclusions, including liquid‐rich two‐phase (L‐type), vapour‐rich two‐phase (V‐type), and daughter mineral‐bearing multi–phase (S‐type) inclusions, have been distinguished. The fluid inclusions in the quartz phenocrysts of the ore‐hosting granite porphyry contain liquid‐rich two‐phase, gas‐rich two‐phase, and daughter mineral‐bearing multi‐phase fluid inclusions. Stages I, II, and III quartz contain all types of fluid inclusions, whereas only L‐type inclusions can be observed in Stage IV quartz. The fluid inclusions in the quartz phenocrysts of the granite porphyry yield homogenization temperatures ranging from 282 to 586 °C and salinities ranging from 3.55% to 58.41% NaCl equiv. The fluid inclusions in the quartz of Stages I, II, III, and IV mainly homogenized at temperatures of 290 to 492 °C, 270 to 424 °C, 248 to 398 °C, and 119 to 219 °C, respectively, with salinities of 9.98–50.85 wt.% NaCl equiv, 6.30–46.37 wt.% NaCl equiv, 6.45–35.99 wt.% NaCl equiv, and 6.59–18.04 wt.% NaCl equiv, respectively. The ore–forming fluids of the Changfagou Cu deposit are therefore characterized by their high temperature and high salinity, and they belong to the H2O–NaCl–CO2 system. The δ18Ofluid values of quartz phenocrysts and vein quartz range from −9.97‰ to +6.91‰, and their δDfluid values range from −142‰ to −93‰, indicating that the early‐stage ore‐forming fluids mainly consisted of magmatic water that experienced the input of magmatic and meteoric water during the last stage. The δ34S values of chalcopyrite and molybdenite range from +2.2‰ to +4.3‰, with an average value of +3.17. The 206Pb/204Pb, 207Pb/204Pb, and 208Pb/204Pb ratios of granite porphyry, arsenopyrite, and pyrite range from 16.672–17.567, 15.516–15.658, and 37.210–38.733, respectively. Both the S and Pb isotopic systems indicate that the ore‐forming materials were derived from mixed mantle and crustal sources. We thus proposed that multiple stages of the boiling of ore‐forming fluid represented the dominant mechanism of the formation of the Changfagou Cu deposit.